Investigating the Teaching and Learning Situation of ESP Writing at the Tertiary Level: The Case of Third Year Students of Commercial Sciences at Jijel University - Rouabah, Naima; Aliouchouche-Kaci, Fadhila (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2023)
It is vital to English for specific purposes (ESP) courses to better prepare non-English major students to perform the English language-related tasks of modern academic and future professional contexts. Hence, the current study reported a small-scale investigation into the teaching and learning situation of ESP writing at the tertiary level. Two data-gathering tools were employed. A questionnaire was administered to 42 students at the third- year level enrolled at the commercial sciences department of Jijel University. To triangulate the quantitative data from the questionnaire, a semi-structured interview was conducted with two teachers of English. The findings revealed that the teaching situation of ESP writing is not satisfactory. Although the quantitative data from the questionnaire unveiled the students‟ interest in developing their writing skills, the qualitative data from the teachers „ interviews revealed that the teaching of writing skills is taken for granted . Therefore, the students expressed dissatisfaction with the ESP course„s effectiveness in meeting their writing needs and scaffolding their competence in writing skills. Hence, the current study's findings suggest the design of an ESP course that stimulates the written communication skills of business students and caters to their writing needs for academic and professional settings.
Keywords: تعليم اللغات -- استراتيجيات التدريس -- المهارات الكتابية -- مهارات التواصل -- الإعداد المهني